Full coverage of perovskite layer onto ZnO nanorods via a modified sequential two-step deposition method for efficiency enhancement in perovskite solar cells - Pipat Ruankham (2018)
© 2017 Elsevier B.V. Full coverage of perovskite layer onto ZnO nanorod substrates with less pinholes is crucial for achieving high-efficiency perovskite solar cells. In this work, a two-step sequential deposition method is modified to achieve an appropriate property of perovskite (MAPbI3) film. Surface treatment of perovskite layer and its precursor have been systematically performed and their morphologies have been investigated. By pre-wetting of lead iodide (PbI2) and letting it dry before reacting with methylammonium iodide (MAI) provide better coverage of perovskite film onto ZnO nanorod substrate than one without any treatment. An additional MAI deposition followed with toluene drop-casting technique on the perovskite film is also found to increase the coverage and enhance the transformation of PbI2to MAPbI3. These lead to longer charge carrier lifetime, resulting in an enhanced power conversion efficiency (PCE) from 1.21% to 3.05%. The modified method could been applied to a complex ZnO nanorods/TiO2nanoparticles substrate. The enhancement in PCE to 3.41% is observed. These imply that our introduced method provides a simple way to obtain the full coverage and better transformation to MAPbI3phase for enhancement in performances of perovskite solar cells.